Relationship between Tax Planning and Deferred Tax Expenses on Profit Management - Nurfadila Nurfadila; Muslim Muslim (Bongaya Journal for Research in Accounting (BJRA), 2021)
This study examines and analyzes the relationship between tax planning and deferred tax expense on earnings management. This study involved 20 manufacturing companies that publish an annual financial report (annual report) that is audited and published on the Indonesia Stock Exchange (IDX) from 2015 to 2017. Sampling uses a purposive sampling method with sample criteria. First, companies that report audited financial statements from 2015 to 2017 and publish financial statements for the year ended and as of December 31. Second, manufacturing companies engaged in the food and beverage sub-sector consumer goods industry. Third, the company was not delisted during the observation period. Fourth, the company reports deferred tax expenses in specific years, namely between 2015-2017. Fifth, the company does not carry out acquisitions, mergers, restructuring, and changes in business groups. Sixth, the company reports financial statements in Rupiah (IDR). Furthermore, data collection in this study used the documentation method. After the data is collected, data analysis is carried out using descriptive statistical methods, logistic regression methods, hypothesis testing (conducted multivariate using logistic regression test (Hosmer and Lemeshow's goodness of fit test), coefficient of determination test, individual parameter significant test, and correlation test. Partial). The results showed a positive correlation between tax planning and deferred tax expense on earnings management.